Exploring rice millers preferences in Kenya - Malabayabas, Arelene Julia; Rafanomesantzoa, Arielle Sandrine; Bayot, Ruvicyn; Muthoni, Lucy; Connor, Melanie (2024)
The rice milling industry in Kenya has undergone significant advancements, playing a crucial role in the rice value chain. The quality traits of rice varieties, including grain size, shape, color, and moisture content, hold immense influence over the final product's quality, price, and marketability. Consumer preferences and the economic value of rice are influenced by these traits. Understanding millers' preferences related to these traits and associated parameters are crucial for guiding future product design decisions.